2022
DOI: 10.1001/jamapsychiatry.2021.3193
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Comorbid Behavioral and Medical Conditions With Cannabis Use Disorder in Pregnancy

Abstract: IMPORTANCE Prenatal cannabis use continues to increase, yet studies of the demographic, psychiatric, and medical characteristics associated with cannabis use in pregnancy are limited by size and use of self-report, and often do not consider cannabis use disorder (CUD) or concomitant substance use disorders (SUDs). Understanding the factors associated with CUD in pregnancy is paramount for designing targeted interventions. OBJECTIVE To examine the prevalence of co-occurring psychiatric and medical conditions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 48 publications
(73 reference statements)
0
3
0
Order By: Relevance
“…Similarly, other recent large systematic reviews have found significant increases in adverse neonatal outcomes among women who used cannabis in pregnancy including small for gestational age, low birth weight, preterm birth, and NICU admissions 14,16,17 . Other studies have reported an association of comorbid behavioral conditions with prenatal cannabis use including increased depression and anxiety, but this was not assessed in our study 45 …”
Section: Discussionmentioning
confidence: 40%
See 1 more Smart Citation
“…Similarly, other recent large systematic reviews have found significant increases in adverse neonatal outcomes among women who used cannabis in pregnancy including small for gestational age, low birth weight, preterm birth, and NICU admissions 14,16,17 . Other studies have reported an association of comorbid behavioral conditions with prenatal cannabis use including increased depression and anxiety, but this was not assessed in our study 45 …”
Section: Discussionmentioning
confidence: 40%
“…14,16,17 Other studies have reported an association of comorbid behavioral conditions with prenatal cannabis use including increased depression and anxiety, but this was not assessed in our study. 45 Compared with other studies focused on prenatal cannabis use disorder, our study included a sizeable and diverse patient population and also adjusted for confounders including tobacco, alcohol, and substance use. In addition, our study assessed many clinically relevant prenatal and neonatal outcomes, including infant death, which has not been consistently reported.…”
Section: Discussionmentioning
confidence: 99%
“…The Original Investigation titled “Association of Comorbid Behavioral and Medical Conditions With Cannabis Use Disorder in Pregnancy,” published on November 3, 2021, was corrected to fix an error in the number of patients with multiple sclerosis and substance use disorder reported in Table 1; the correct number is 69 patients. In addition, there were errors in the quintiles presented in the legend to Figure 2; the correct quintile values are 0 to <0.011, 0.011 to <0.015, 0.015 to <0.019, 0.019 to <0.028, and 0.028 to <0.047.…”
mentioning
confidence: 99%